HUBUNGAN SELF EFFICACY, MOTIVASI BERPRESTASI, PROKRASTINASI AKADEMIK DAN STRES AKADEMIK MAHASISWA - Sagita, Dony Darma; Daharnis, Daharnis; Syahniar, Syahniar (Jurusan Bimbingan dan Konseling, 2017)
This research is motivated by the stress that become a complex problem for students in daily life. Self efficacy, achievement motivation, and academic procrastination expect to affect student?s academic stress. The research purpose was to describe: (1) self efficacy, (2) achievement motivation, (3) academic procrastination, (4) student academic stress, (5) correlation of self efficacy with student?s academic stress, (6) correlation of achievement motivation with student?s academic stress, (7) correlation of academic procrastination with student?s academic stress, and (8) correlation of self efficacy, achievement motivation and academic procrastination with student?s academic stress.This study used quantitative approach with correlation descriptive method and the population were students of Guidance and Counseling Program of Education Faculty State University of Padang. The sampling technique was proportional stratified random sampling. The instrument was a scale model of Likert. The instrument reliability of self efficacy was 0,930, achievement motivation was 0,906, academic procrastination was 0,868, and student?s academic stress was 0,932. The instrument validity of self efficacy 0,554, achievement motivation was 0,469, academic procrastination was 0,453, and student?s academic stress was 0,568. Data were analyzed by using simple linier regression and multiple regression.The result indicates that: (1) self efficacy and achievement motivation of students are at the high category, (2) academic procrastination and student?s academic stress are in the moderate category, (3) there are negative correlation and significant between self efficacy with student?s academic stress, (4) there are negative and significant correlation between achievement motivation and student?s academic stress, (5) there are positive and significant correlation between academic procrastination with student?s academic stress, (6) there are significant correlation between self efficacy, achievement motivation and academic procrastination with student?s academic stress together, and (7) the implication are inputs from the various parties involved in to increase self efficacy and achievement motivation of students and reduce or prevent procrastination and academic stress..Keywords: Self Efficacy, Achievement Motivation, Procrastination Academic, Academic Stress